Age-Related Reductions in Tactile and Motor Inhibitory Function Start Early but Are Independent - Ruitenberg, Marit F. L.; Cassady, Kaitlin E.; Reuter-Lorenz, Patricia A.; Tommerdahl, Mark; Seidler, Rachael D. (Frontiers in Aging Neuroscience, 2019)
Aging is associated with declines in motor and somatosensory function. Some of these motor declines have been linked to age-related reductions in inhibitory function. Here we examined whether tactile surround inhibition also changes with age, and whether these changes are associated with those in the motor domain. We tested a group of 56 participants spanning a wide age range (18-76 years old), allowing us to examine when age differences emerge across the lifespan. Participants performed tactile and motor tasks that have previously been linked to inter- and intrahemispheric inhibition in the somatosensory and motor systems. Results showed that aging is associated with reductions in inhibitory function in both the tactile and motor systems starting around 40 years of age; however, age effects in the two systems were not correlated. The independent effects of age on tactile and motor inhibitory function suggest that distinct mechanisms may underlie age-related reductions in inhibition in the somatosensory and motor systems.